The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00383-016-3922-1
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein LIN28 is a sensitive marker of pediatric yolk sac tumors

Abstract: LIN28 is a sensitive marker for pediatric YSTs and it can be used to distinguish them from mature teratomas. LIN28 is likely to become a new and valuable biomarker for diagnosing of pediatric YST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…LIN28 is a novel sensitive and relatively specific diagnostic marker for pediatric YSTs, with advantages over AFP in diagnosing pediatric YSTs. 12 The present tumor was also positive for LIN28, favoring a diagnosis of YST. SALL4 is a 100% sensitive diagnostic marker for extragonadal YST.…”
Section: Discussionsupporting
confidence: 51%
“…LIN28 is a novel sensitive and relatively specific diagnostic marker for pediatric YSTs, with advantages over AFP in diagnosing pediatric YSTs. 12 The present tumor was also positive for LIN28, favoring a diagnosis of YST. SALL4 is a 100% sensitive diagnostic marker for extragonadal YST.…”
Section: Discussionsupporting
confidence: 51%
“…Performing a central pathomorphological examination can be helpful in the case of these neoplasms. Perhaps new tumor markers, like the ones discovered by Feng et al will help eliminate mistakes in pathomorphological diagnoses [ 24 ]. Grading was available only in one patient in our study and no Heifetz lesions were observed.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Maybe new tumor markers, like the ones discovered by Feng et al (RNA-binding protein LIN28) will help eliminate mistakes in pathomorphological diagnoses. 17 …”
Section: Discussionmentioning
confidence: 99%
“…7 Maybe new tumor markers, like the ones discovered by Feng et al (RNA-binding protein LIN28) will help eliminate mistakes in pathomorphological diagnoses. 17 In a recent study, ovarian tissue sparing technique for mature teratoma was applied in only 11.11% of patients operated before 2003 and increased to 40.54% after this year. The preservation rate was higher in the group of girls in whom laparoscopic technique was chosen.…”
Section: Dovepressmentioning
confidence: 99%